On the precise determination of the Tsallis parameters in proton–proton collisions at LHC energies. (16th March 2018) - Bhattacharyya, T; Cleymans, J; Marques, L; Mogliacci, S; Paradza, M W
Abstract: A detailed analysis is presented of the precise values of the Tsallis parameters obtained in p – p collisions for identified particles, pions, kaons and protons at the LHC at three beam energies s = 0.9, 2.76 and 7 TeV. Interpolated data at s = 5.02 TeV have also been included. It is shown that the Tsallis formula provides reasonably good fits to the p T distributions in p – p collisions at the LHC using three parameters d N /d y, T and q . However, the parameters T and q depend on the particle species and are different for pions, kaons and protons. As a consequence there is no m T scaling and also no universality of the parameters for different particle species.